Serum lactate dehydrogenase and creatine kinase during marathon training. Issue 3 (September 1985) - Rumley, A G; Pettigrew, A R; Colgan, M E; Taylor, R; Grant, S; Manzie, A; Findlay, I; Dargie, H; Elliott, A
Abstract : Serum total creatine kinase (CK) and the lactate dehydrogenase (LDH) isoenzymes were studied in 38 sedentary middle-aged men (aged 35-50 yrs) during a 30 week marathon training programme. Basal CK activity rose by 33% after 15 weeks but a significant rise (27%) in LDH activity took 30 weeks to occur. Post-exercise (maximum test on a bicycle ergometer) CK and LDH activities were higher than pre-exercise levels but the increment in enzyme activity following exercise did not change. LDH1 and LDH2 isoenzyme activity increased by 2.5% and 4% of total LDH respectively while LDH3 and LDH5 decreased by 3.9% and 2.4% respectively over 30 weeks. Post marathon total CK did not correlate with finishing time at 30 mins or 30 hrs post race. The range of CK MB isoenzyme activity at 30 mins post race was 1.8-9.8% of total CK with 11 subjects having a value above 6%. The training programme appears not to have affected muscle CK and LDH release during exercise but isoenzyme distribution changes reflect the adaptations known to occur in muscle during endurance training. Unfortunately only 16 subjects were available for all the investigations, and it is these upon whom most of the data were obtained.